Comparison of the Pregnant and Non-Pregnant Women of Reproductive Age Hospitalized Due to COVID-19 Infection - Kiliç, Ö.; Polat, M.; Tıbel Tuna, N.; Köprü, E.; Elmali, M.; Bozkurt, I.; Güven, D. (Ondokuz Mayis University, 2022)
COVID-19 affects pregnant women more severely than nonpregnant women of reproductive age. However, the rate of critical illness and fatality reported in other studies varied in a wide range in both groups. The study aims to investigate the clinical outcomes of COVID-19 in the pregnant and nonpregnant matched control patients admitted to the hospital. Pregnant and nonpregnant patients of reproductive age (18-45 years) infected with COVID-19 who were admitted to Ondokuz Mayıs University Hospital, Samsun, Turkey, from March 11 to December 11, 2020, were enrolled in the study. The clinical, radiological, and laboratory data of the patients were analyzed retrospectively. A total of 153 patients were investigated; 123 were nonpregnant, and 30 were pregnant. Emergency delivery occurred in 5 (17%) pregnant women due to acute respiratory failure associated with COVID-19 and 1 (3%) pregnant woman due to obstetric reasons. Four premature births, one perinatal death, and no stillbirth or miscarriage were reported. The rate of admission to the intensive care unit (ICU) [7/30 (23.3%) vs 3/123 (2.4%), p<0.001] and the need for invasive mechanical ventilation (IMV) [5/30 (17.0%) vs 2/123 (1.6%), p=0.003] were significantly higher in pregnant than in non-pregnant patients. However, hospital length of stay (HLOS) and mortality did not differ between groups: HLOS was median 4 vs 5 days, p=0.68, and the mortality rate was 1/123 (0.8%) vs 0/30 (0%), p=0.62 in nonpregnant and pregnant patients respectively. We observed that COVID-19 has a more severe course in pregnant women versus the nonpregnant control group, but no difference was noted in terms of hospital length of stay and mortality. The overall case fatality rate of COVID-19 in hospitalized pregnant or nonpregnant women of reproductive age was found to be much lower than the general hospitalized population worldwide. © 2022 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: COVID-19 Infection; Critical Illness; Mortality; Nonpregnant Patient; Pregnancy